THE ROLE OF HYMENOLEPIDOSIS AND GIARDIA IN THE FORMATION OF CLINICAL PATHOGENETIC AND TREATMENT ASPECTS IN PATIENTS DIAGNOSED WITH SKIN DYSCHROMIA - Mirzoyeva Mexriniso Rizoyevna; Nurova Ozoda Kamalovna (Web of Journals Publishing, 2024)
This article examines the role of hymenolepiasis and giardiasis in the clinical, pathogenetic, and therapeutic aspects of skin dyschromia in affected patients. Parasitic infections, particularly hymenolepiasis and giardiasis, are known to induce systemic toxic and immunological changes, potentially contributing to disruptions in skin pigmentation. The study evaluates the prevalence of these parasitic invasions in patients with skin dyschromia, their impact on the pathogenesis of pigmentary disorders, and therapeutic strategies for effective treatment. Furthermore, it highlights the benefits of antiparasitic therapy in alleviating symptoms of skin dyschromia.
Keywords: Skin dyschromia, hymenolepiasis, Giardiasis, Pathogenesis, Parasitic invasions, Dermatological disorders.